Sustainability Goals in Economic Policy - Ueberblick (Wirtschaftsdienst)
Abstract The Scientific Advisory Board at the Federal Ministry for Economic Affairs and Climate Protection held an internal symposium on sustainability goals in economic policy at its 500th meeting in April 2022 to explore various aspects of this topic in greater depth. Especially in the context of combating climate change, the achievement of sustainability goals is a top political priority. These go beyond the climate goals — reference is often made in this context to the Sustainable Development Goals (SDGs) of the United Nations. The authors discuss from different perspectives how the mandate for sustainability affects legislation, regulation and corporate behaviour.